The British Papers : Secret and Confidential, India, Pakistan, Bangladesh Documents 1958-1969 - Compiled and selected by Khan, Roedad; Introduction by Khan, Humayun (Karachi Oxford University Press, 2002)
The British Papers includes reports of meetings with Heads of State and Government, important ministers, high dignitaries, political leaders, and critical analysis of the state of mind of the people in power and their political opponents. Also captured in these reports is the thinking and assessments of key players in the drama, the internal power struggle, shifting loyalties and Byzantine palace intrigues. This unprecedented trove of hitherto secret documents leads us through a well-stocked museum of what now seems a distant time." "The book provides an extraordinary account of political events in the subcontinent, re-ignites old memories, reveals the power struggles, changing fortunes, and fateful decisions that still haunt political life in the subcontinent. Taken as a whole, these papers reveal in extraordinary detail what the diplomats saw as they looked out from their vantage positions on the events unfolding around them and how they forecast the march of events. In these documents, one gets to observe the clash of personalities, the conflicts among the key players, their ambitions, their hopes, their prejudices and their frustrations. They are, above all, a journey through history. Future historians removed from the passions of the moment will find a study of these voluminous dispatches far more interesting.
Include Index.
Confidential British diplomatic dispatches have surfaced that provide a revealing view of events in the subcontinent from 1947 right up to 1969. These documents, obtained from the British Archives, include reports of meetings with Heads of State and government, ministers, high dignitaries and political leaders, and critical analysis of the state of mind of the people in power and their political opponents. Also captured in these reports is the thinking and assessments of key players in the drama, the internal power struggle, shifting loyalties and Byzantine palace intrigues.
Keywords: Pakistanadesh -- India -- Bangladesh